Prevalence and severity of anaemia among the Temiar sub-ethnic indigenous Orang Asli communities in Kelantan, Peninsular Malaysia - Idris, Zulkarnain Md; Wahid, Wathiqah; Seri Rakna, Mohd Ikhwan Mukmin; Ghazali, Nuraffini; Hassan, Noor Wanie; Abdul Manap, Siti Nor Azreen; Mohamed, Ahmad Imran; Chuangchaiya, Sriwipa; Mohd Kasri, Muhd Rafiq (Frontiers in Public Health, 2024)
Introduction Anaemia remains a primary concern of public health in developing countries. Indigenous populations are a significant and frequently underreported group at risk for anaemia. This study aimed to assess the prevalence of anaemia and identify its determinants in the Temiar sub-ethnic indigenous Orang Asli (OA) community in Peninsular Malaysia. Methodology A community-based cross-sectional study was conducted among 640 indigenous Temiar OA participants from a remote settlement in Gua Musang, Kelantan, Malaysia. Data was collected using face-to-face interviews with a standardised pretested questionnaire and through blood samples collected for haemoglobin (Hb) testing. Anaemia status was determined using the Hb level cut-off established by the World Health Organization (WHO). Descriptive analysis was used to determine the prevalence of anaemia, while multiple logistic regression was used to determine factors associated with anaemia. Results The overall anaemia prevalence was 44.7% (286/640), and the prevalence rates of mild, moderate and severe anaemia were 42.7, 50.7 and 6.6%, respectively. Anaemia-specific prevalence varied significantly by age group (p < 0.001) and was highest in the ≤5 group for both moderate anaemia (43.4%) and severe (42.1%), followed by the 6–17 age group for mild anaemia (39.3%). The prevalence of anaemia was also highest among students (53.9%), with a significant difference observed between the three anaemia severity classifications (p = 0.002). In the multivariate logistic regression, only age groups of 6–17 (adjusted odds ratio [aOR] 0.38, p < 0.001), 18–40 (aOR 0.18, p < 0.001) and > 40 (aOR 0.25, p < 0.001) were significantly associated with the lower odds of anaemia in the population. Conclusion This study has highlighted the high prevalence of anaemia among indigenous OA in Peninsular Malaysia and revealed that younger children were positively associated with childhood anaemia. Effective interventions and special attention to this indigenous population need to be implemented to reduce the risk of anaemia.